2016
DOI: 10.13189/ujer.2016.040602
|View full text |Cite
|
Sign up to set email alerts
|

The Facebook-in-action: Challenging, Harnessing and Enhancing Students Class Assignments and Projects

Abstract: Issues of universities students harnessing and capitalizing the usage of Facebook for their own learning capabilities and effective thinking is always the focus of education scholars, in assessing the quality class assignments and projects produced by them. Therefore, Facebook is now becoming unbearable influence since the internet activation in the past few years, almost totally interconnected the information sharing and needs among those students. In this action research, the researchers explore the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Facebook makes it students easier to submit the assignment and the instruction for the next assignment. Similarly, the research of Saifudin et al (2016) showed that students were very aware of Facebook communication and how important it was to prepare and complete class assignments and projects. Furthermore, Facebook supports students' social media competence, understanding of the material, and the lecturer's explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Facebook makes it students easier to submit the assignment and the instruction for the next assignment. Similarly, the research of Saifudin et al (2016) showed that students were very aware of Facebook communication and how important it was to prepare and complete class assignments and projects. Furthermore, Facebook supports students' social media competence, understanding of the material, and the lecturer's explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Along with Cotton (1996), Maroulis andGomez (2008), andRaywid (1997), the extended and meticulous work of Froment et al (2017) evidenced that SNSs favour a more individualised follow-up, which facilitates a deeper personal knowledge of students and teachers. Likewise, the idea that communication and effective relationships are promoted in a positive way within these environments is highly sustained (Abella & Delgado, 2015;Albayrak & Yildirim, 2015;Amador & Amador, 2014;Aydin, 2012;Bowers-Campbell, 2008;Conole & Culver, 2010;Hernández & Medina, 2015;Irwin, Ball, Desbrow, & Leveritt, 2012;Lee, Lee, & Kim, 2015;Ormart & Navés, 2014;Rezende, van Kruistum, & van Oers, 2016;Rienties & Kinchin, 2014;Roblyer et al, 2010;Saifudin, Yacob, & Saad, 2016;Sobaih, Moustafa, Ghandforoush, & Khan, 2016;J. Wang, 2013;Wodzicki, Schwämmlein, & Moskaliuk, 2012).…”
Section: The Distance and Closeness Of The Teacher-student Relationshipmentioning
confidence: 99%
“…Wang, 2013;Wodzicki, Schwämmlein, & Moskaliuk, 2012). The study by Saifudin et al (2016) showed that the use of Facebook groups for educational purposes strengthened the links and relationship between students and teachers. This approach was particularly relevant to students in the early and late stages of undergraduate studies.…”
Section: The Distance and Closeness Of The Teacher-student Relationshipmentioning
confidence: 99%
“…FB group features allow students to have extra time to learn and give them opportunities to use learning resources outside the classroom (Davidovitch & Belichenko, 2018). The use of FB in the teaching process can improve students' social competence, the effectiveness of their thinking, teamwork, and information technology skills (Alarabiat & Al-Mohammad, 2015;Saifudin et al, 2016;Gersamia & Toradze, 2017).…”
Section: Facebook As An Educational Toolmentioning
confidence: 99%